Epigenetics in myeloproliferative neoplasms - Greenfield, Graeme; McMullin, Mary Frances (Frontiers in Oncology, 2023)
The myeloproliferative neoplasms (MPNs) are a group of acquired clonal disorders where mutations drive proliferative disease resulting in increased blood counts and in some cases end stage myelofibrosis. Epigenetic changes are the reversible modifications to DNA and RNA associated proteins which impact gene activity without changing the DNA sequence. This review summarises mechanisms of epigenetic changes and the nucleosome. The drivers and epigenetic regulators in MPNs are outlined. In MPNs distinct patterns of epigenetic dysregulation have been seen in chronic and in advanced phases. Methylation age and histone modification is altered in MPNs and by further treatment. The alterations found in methylation age in MPNs and with treatment are discussed and the changes in histone modification with JAK inhibition are evaluated. Currently available therapeutic areas where the epigenome can be altered are outlined.Thus we review the current knowledge and understanding of epigenetics in MPN and consider further management options. Understanding of the epigenome and its alteration in MPNs and epigenetic changes associated with progression of disease will lead to advances in therapeutic options.